👤

W załączniku jest zadanie

W Załączniku Jest Zadanie class=

Odpowiedź :

Odpowiedź:

Zadanie 23

a + (a - b) = a + a - b= 2a - b  

2x - (x + 4) = 2x - x - 4 = x - 4  

7 - (-x + 6) = 7 + x - 6 = 1 + x    

-(x + 4) + (x - 5) = -x - 4 + x - 5 = -9  

1 - (t + p) - (t - 2) = 1 - t + p - t + 2 = -2t + p + 3  

-(-y + 2) + (-2y - 4) = y - 2 - 2y - 4 = -6 - y

Zadanie 24

(a + b) - (2a - b) - (a - 2b) = a + b - 2a + b - a + 2b = -2a + 4b

(3x - y + 1) - (x + y) + (y - x) = 3x - y + 1 - x - y + y - x = - y + 1 + x

- (kx + ny) - (3kx + 2ny) + (5kx - 3ny) = -kx - ny - 3kx - 2ny + 5kx - 3ny = 3kx - 6ny

(2ab + a + 3) - (3ab - a + 3) = 2ab + a + 3 - 3ab + a - 3 = 2a - ab

(4x² - 3x) - (x + 0,1x²) - (x² - 0,1x) = 4x² - 3x - x - 0,1x² - x² + 0,1x = 2,9x² - 3,9x

Szczegółowe wyjaśnienie:

(Mam nadzieję, że pomogłam)